OP0175 Monocarboxylate Transporter (MCT)-4, Associated with the Decrease of Synovial Fluid Ph, is A Novel Therapeutic Target of Rheumatoid Arthritis. (10th June 2014) - Fujii, W.; Ashihara, E.; Nagahara, H.; Kukida, Y.; Ishigaki, R.; Kasahara, A.; Sagawa, T.; Seno, T.; Yamamoto, A.; Kohno, M.; Oda, R.; Tokunaga, D.; et al.
Abstract : Background: It is well known that synovial fluid pH is decreased in rheumatoid arthritis (RA) patients (1), but the meaning and mechanism remain unclear. Objectives: We investigate the correlation between synovial fluid pH and the disease activity of RA. We reveal the mechanism by which synovial fluid pH is regulated and explore the novel therapeutic strategy of RA by applying this mechanism. Methods: We measured the values of pH and the concentration of L-lactate in synovial fluid of RA patients. Next, we investigated the expression of ion transporters regulating intracellular and extracellular pH in RA synovial fibroblasts (RASFs) obtained from the inflamed joints using quantitative RT-PCR and Western Blotting. Finally, we suppressed the ion transporter expression by small interfering RNA (siRNA) against the ion transporter increased in RASFs, and analyzed their viability and proliferative capacity of RASFs. Results: Synovial fluid pH was decreased as the disease activity score (DAS)-28 CRP increased in RA patients (graph A, n=17, r = -0.81, p<0.001), accompanied by increased level of synovial fluid L-lactate (graph B, n=11, r = -0.79, p<0.01). The mRNA levels of Na + /H + exchanger (NHE)-1, vacuolar type H + -ATPase (V-ATPase), and monocarboxylate transporter (MCT)-1 were not altered. However, the mRNA and protein levels of MCT4, exporting intracellular lactate to extracellular space, were significantly increased in RASFs compared to those in osteoarthritis (OASFs) or normal synovial fibroblasts (graph C). Knockdown of MCT4 of RASFs induced apoptosis in RASFs and subsequently their proliferation was inhibited (graph D), indicating important roles of MCT4 in RASF proliferation. Conclusions: Synovial fluid pH negatively correlated with DAS28-CRP, accompanied by increased level of L-lactate. We suggest that it is due to the increased expression of MCT4 in RASFs. Also, silencing of MCT4 induces apoptosis in RASFs and inhibits RASF proliferation, indicating that MCT4 could be a novel therapeutic target of RA. References: Falchuk KH, Goetzl EJ, and Kulka JP. 1970. Respiratory gases of synovial fluids. An approach to synovial tissue circulatory-metabolic imbalance in rheumatoid arthritis. Am J Med. Aug;49(2):223-31. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1017